MAPT mutation-induced behavioral variant frontotemporal dementia in an Asian patient: a multimodal biomarker case report resolving diagnostic challenges with Alzheimer’s disease - Zhang, Yan; Chen, Siwei; Yan, Guiying; Zhang, Zhifei; Amina,; Wang, Ting; Wang, Shuang; Zhang, Chen; Sun, Yong’an (Frontiers in Genetics, 2025)
BackgroundThe clinical phenotypic overlap between frontotemporal dementia (FTD) and Alzheimer’s disease (AD) frequently leads to misdiagnosis, while biomarkers (e.g., Aβ-PET) and genetic testing provide critical differential diagnostic evidence. Although MAPT gene mutations represent common genetic etiologies of FTD, their occurrence in Asian populations remains underreported. Specifically, FTD caused by the MAPT IVS10 + 16C>T mutation shows limited documentation in Asian populations, with its phenotypic heterogeneity and treatment responses remaining poorly characterized.MethodsWe present a case of FTD manifesting progressive memory decline, compulsive behaviors, and apathy. MRI revealed bilateral frontoparietotemporal atrophy with prominent medial temporal lobe and hippocampal involvement, initially misdiagnosed as AD. Subsequent Aβ-PET negativity emerged as a pivotal diagnostic turning point, and identification of a heterozygous MAPT mutation (IVS10 + 16C>T) confirmed behavioral variant FTD (bvFTD) diagnosis. Partial improvement in compulsive behaviors and verbal fluency was observed following memantine treatment. A literature review summarizes clinical characteristics of FTD associated with IVS10 + 16C>T mutations.ResultsComprehensive neuropsychological assessment, cranial MRI, and negative Aβ-PET excluded AD pathology. Genetic confirmation of MAPT IVS10 + 16C>T mutation established bvFTD diagnosis. Three-month memantine treatment reduced compulsive behaviors without cognitive improvement. Literature analysis indicates this mutation’s rarity in Asian populations, typically presenting with behavioral abnormalities frequently misdiagnosed as AD.ConclusionThis study rectified misdiagnosis of MAPT IVS10 + 16C>T-associated bvFTD through multimodal diagnostics, emphasizing the synergistic value of genetic testing and neuroimaging. Memantine’s partial behavioral symptom alleviation suggests potential mutation-specific therapeutic efficacy requiring further validation. Future directions should optimize diagnostic protocols (e.g., cost-effective genetic screening) and address barriers to early diagnosis in Asian populations.